Publication patterns in Restorative Dentistry and Endodontics - Sherin Jose Chockattu; Byathnal Suryakant Deepak (Restorative Dentistry & Endodontics, 2019)
ObjectivesRestorative Dentistry and Endodontics (Restor Dent Endod; RDE) is an English-language journal published by the Korean Academy of Conservative Dentistry, and it has been online since 2012 with quarterly publications. The purpose of this paper was to review and analyze the publications in this journal since its inception and over the 7-year period from 2012 to 2018.Materials and MethodsThis paper assessed the number, type, and subject of articles published, as well as authorship patterns and article citations of the journal over a 7-year period. The citation indicator for the journal (h-index) was assessed using Google Scholar.ResultsThe number of articles per issue has remained relatively consistent in the 7 years that were analyzed. An analysis of the article types revealed various categories of review articles. Original research articles accounted for the most articles per volume. Twice as many articles per volume were on endodontic topics than on restorative subjects. Articles published in RDE have been widely cited in Synapse, Crossref, and PubMed Central. A country-wise mapping of authors' institutions revealed significant contributions from authors around the world. With an h-index of 24, RDE ranks third among journals in its specialty. The most cited articles were open lectures on statistics and research articles on recent concepts, technology, and materials.ConclusionOver the last 7 years, RDE has served as a platform for a large number of manuscripts in the field of restorative dentistry and endodontics.